Acoustic parameter changes after bariatric surgery. (2nd October 2022) - Eravci, Fakih Cihat; Yildiz, Barış Doğu; Özcan, Kürşat Murat; Moran, Münevver; Çolak, Mustafa; Karakurt, Süleyman Emre; Karakuş, Mehmet Fatih; Ikinciogullari, Aykut
Abstract: Objective: To investigate the acoustic parameter changes after weight loss in bariatric surgery patients. Materials and methods: This prospective, longitudinal study was conducted with 15 patients with planned bariatric surgery, who were evaluated pre-operatively and at 6 months post-operatively. Fundamental frequency (F0), Formant frequency (F1, F2, F3, and F4), Frequency perturbation (Jitter), Amplitude perturbation (Shimmer) and Noise-to-Harmonics Ratio (NHR) parameters were evaluated for /a/, /e/, /i/, /o/, and /u/ vowels. Changes in the acoustic analysis parameters for each vowel were compared. The study group was separated into two groups according to whether the Mallampati score had not changed (Group 1) or had decreased (Group 2) and changes in the formant frequencies were compared between these groups. Results: A total of 15 patients with a median age of 40 ± 11 years completed the study. The median weight of the patients was 122 ± 14 kg pre-operatively and 80 ± 15 kg, post-operatively. BMI declined from 46 ± 4 to 31 ± 5 kg/m 2 . The Mallampati score decreased by one point in six patients and remained stable in nine. Of the acoustic voice analysis parameters of vowels, in general, fundamental frequency tended to decrease, and shimmer and jitter values tended to increase. Some of the formant frequencies were specifically affected by the weight loss and this showed statistical significance between Group 1 and Group 2. Conclusion: The present study reveals that some specific voice characteristics might be affected by successful weight loss after bariatric surgery. Highlights: Obesity reduces the size of the pharyngeal lumen at different levels. The supralaryngeal vocal tract size and configuration is a determinative factor in the features of the voice. Changes in the length and shape of the vocal tract, or height and position of the tongue can result in changes especially in formant frequencies in acoustic analysis.